American religious liberalism - Schmidt, Leigh Eric; Promey, Sally M. (Religion in North America, 2012)
Religious liberalism in America has often been equated with an ecumenical Protestant establishment. By contrast, American Religious Liberalism draws attention to the broad diversity of liberal cultures that shapes America's religious movements. The essays gathered here push beyond familiar tropes and boundaries to interrogate religious liberalism's dense cultural leanings by looking at spirituality in the arts, the politics and piety of religious cosmopolitanism, and the interaction between liberal religion and liberal secularism. Readers will find a kaleidoscopic view of many of the progre